2018
DOI: 10.1101/252791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsupervised clustering of temporal patterns in high-dimensional neuronal ensembles using a novel dissimilarity measure

Abstract: Temporally ordered multi-neuron patterns likely encode information in the brain. We introduce an unsupervised method, SPOTDisClust (Spike Pattern Optimal Transport Dissimilarity Clustering), for their detection from high-dimensional neural ensembles. SPOTDisClust measures similarity between two ensemble spike patterns by determining the minimum transport cost of transforming their corresponding normalized cross-correlation matrices into each other (SPOTDis). Then, it performs density-based clustering based on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 80 publications
1
28
0
Order By: Relevance
“…Temporal sequences may also be critical for memory formation, because the plasticity rules in the brain are highly sensitive to the temporal order in which neurons fire spikes [12][13][14].We have previously developed a dissimilarity measure between multi-neuron temporal spiking patterns called SPOTDis (Spike Pattern Optimal Transport Dissimilarity). This measure is defined as the minimum energy (optimal transport) that is needed to transform all pairwise cross-correlations of one epoch k into the pairwise cross-correlations of another epoch m. We showed that, due to employment of optimal transport, SPOTDis has several attractive features (see Results) [15], and can be combined with unsupervised dimensionality-reduction techniques like t-SNE or clustering techniques like HDBSCAN to characterize the state-space of multi-neuron temporal sequences [15]. However, the SPOTDis dissimilarity measure has two principal weaknesses: (1) Its computational complexity, for comparing two time epochs, is O(N 2 ), where N is the number of neurons.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Temporal sequences may also be critical for memory formation, because the plasticity rules in the brain are highly sensitive to the temporal order in which neurons fire spikes [12][13][14].We have previously developed a dissimilarity measure between multi-neuron temporal spiking patterns called SPOTDis (Spike Pattern Optimal Transport Dissimilarity). This measure is defined as the minimum energy (optimal transport) that is needed to transform all pairwise cross-correlations of one epoch k into the pairwise cross-correlations of another epoch m. We showed that, due to employment of optimal transport, SPOTDis has several attractive features (see Results) [15], and can be combined with unsupervised dimensionality-reduction techniques like t-SNE or clustering techniques like HDBSCAN to characterize the state-space of multi-neuron temporal sequences [15]. However, the SPOTDis dissimilarity measure has two principal weaknesses: (1) Its computational complexity, for comparing two time epochs, is O(N 2 ), where N is the number of neurons.…”
mentioning
confidence: 89%
“…trials (e.g. stimulus presentations) or sliding windows [15]. The problem is to find a dissimilarity measure with the following properties [15]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus developed a new model-based 90 approach using a template-matching procedure to classify these border cells in RSC ( Fig. 91 1d-1f), based on (Grossberger, Battaglia, & Vinck, 2018). 92…”
mentioning
confidence: 99%
“…2, 3), adding additional weight in the 587 location of placed objects/walls, or removing it in the absence of an outer wall. The EMD 588 distance between a ratemap and a template represents the minimal cost that must be paid to 589 transform one distribution into another, and is thus a normalized metric of dissimilarity 590 (Grossberger et al, 2018). 591…”
mentioning
confidence: 99%